Educational Software for Dyslexic Children : Systematic Literature Review - Siti Hafawati Ishak; Noor Azli Mohamed Masrop; Ghazali Zainuddin; Muhammad Sabri Sahrir; Sarifah Nurhanum Syed Sahuri (Kolej Universiti Islam Antarabangsa Selangor, 2024)
MyJICT - Malaysian Journal of Information and Communication Technology Vol 6 2021, Issue 1 | e-ISSN 0127-7812